Beyond Cultural Values: Identifying Proximal Predictors of Early Literacy Skills in Indonesian Kindergarteners - Astuti, Wuri; Yafie, Evania; Tirtaningsih, Munaisra Tri; Iriyanto, Tomas; Pratiwi, Ajeng Putri (Jurnal Pendidikan Progresif, 2025)
Beyond Cultural Values: Identifying Proximal Predictors of Early Literacy Skills in Indonesian Kindergarteners. Objectives: Early literacy development in young children is influenced by many interrelated factors within the family and cultural environments. In this study, we have also taken into account family values, parent–child relationships, and literacy activities in relation to children’s emergent reading in kindergarten. Methods: In the current study, a multiple regression design research approach was employed with 100 participants (early childhood teachers and parents). The information was collected by official questionnaires. The questionnaire included measures of familial sociocultural value orientation, parent–child interaction, literacy-related activities at home, and children’s early literacy skills, assessed through parent self-report items developed and adapted from established early literacy and home literacy environment instruments. To determine the predictive capability of the factors, multiple regression analysis was conducted as the technique for data analysis. Findings: The current research aims to identify the degree to which family socio-cultural values, parent-child interaction, and home literacy activities can predict outcomes in early literacy for children in kindergartens in Pasuruan, East Java, Indonesia. The results showed that parent-child interaction and home literacy activity variables have a strong positive effect on children's performance in early literacy. In contrast, family socio-cultural values alone did not demonstrate a direct statistical effect in the model. Conclusion: It would appear from our findings that active involvement and literacy-related pursuits are more influential in building early reading skills than attitudes towards learning within the family as a whole. Our recommended solution would be increasing parent-child interaction activities and engaging in literacy pursuit programs. However, these activities must be situated within culturally salient family contexts. The main originality of the study is that it simultaneously examines three family-based variables in a given cultural context, which reinforces the hypothesis that early literacy is influenced by a social and cultural framework. Keywords: early literacy, family socio-cultural values, parent–child relationship, literacy practices, preschool education.